Surgery and paediatric inflammatory bowel disease - Kelay, Arun (Transl Pediatr, 2019)
The incidence of paediatric Crohn’s disease (CD) and ulcerative colitis (UC) is increasing. Surgical intervention is required during childhood in approximately 25% of children diagnosed with CD, and for 10% of those diagnosed with UC. Although there is evidence that the rate of surgical intervention undertaken in children is decreasing since the introduction of biologic therapy, this may only represent a delay rather than true reversal of the risk of surgery. Surgery for CD is not curative and limited resection is the key principle thus preserving bowel length. For UC, subtotal colectomy is relatively curative; ileo-anal pouch anastomosis can be performed to restore bowel continuity.